2017
DOI: 10.1163/15685381-00003111
|View full text |Cite
|
Sign up to set email alerts
|

A new population and subspecies of the critically endangered Anatolian meadow viper Vipera anatolica Eiselt and Baran, 1970 in eastern Antalya province

Abstract: We report on a new population of Vipera anatolica from the Geyik Mountain Range in eastern Antalya Province, Turkey. It represents only the second known location, and is situated in a valley about 200 km east from the terra typica at Kohu Dağ in western Antalya Province. We compare both populations and, based on marked differences in morphology, habitat, genetics, and its geographically isolated location, we describe the recently discovered population as a new subspecies. Aspects of ecology, threats, and conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…species and subspecies are compared by their composition. Taxonomic relations based on Alencar et al 79 and Göçmen et al 41 are shown without genetic distances. The asterisked data set is a result of this study.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…species and subspecies are compared by their composition. Taxonomic relations based on Alencar et al 79 and Göçmen et al 41 are shown without genetic distances. The asterisked data set is a result of this study.…”
Section: Resultsmentioning
confidence: 94%
“…Vipera anatolica senliki is a newly discovered subspecies of V. anatolica . 41 After the description of a new subspecies ( V. a. senliki ), the populations in Kohu Mountain, Çığlıkara Cedar Reserve became nominotypic ( V. a. anatolica ). Therefore, a comparative analysis of venoms between these two subspecies is warranted, and this, in the context of venoms of other closely related and geographically proximal Vipera species, could provide insights into inter-specific and geographic venom variation in this region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other sympatrically living reptiles are; Testudo graeca, Anatololacerta pelasgiana, Stellagama stellio, Eirenis modestus, Platyceps najadum and newly described critically endangered viper subspecies Vipera anatolica senliki. Also, Pelophylax bedriagae and Ablepharus budaki were given as sympatric species in Göçmen et al (2017). Derivatio nominis: The newly described subspecies were named in honor of Prof. Dr. Cemal Varol TOK who made valuable contributions to Turkish Herpetofauna and also the word "var'ol" is a verb that means "to exist, to stay alive, to be in existence".…”
Section: Methodsmentioning
confidence: 99%